2015
DOI: 10.3340/jkns.2015.58.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Total Intrameatal Anterior Inferior Cerebellar Artery Aneurysm

Abstract: Among the distal anterior inferior cerebellar artery (AICA) aneurysms, a unique aneurysm at the meatal loop inside the internal auditory meatus is extremely rare. The authors report a case of surgically treated total intrameatal AICA aneurysm. A 62-year-old female patient presenting with sudden bursting headache and neck pain was transferred to our department. Computed tomography and digital subtraction angiography showed subarachnoid hemorrhage at the basal, prepontine cistern and an aneurysm of the distal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Intrameatal location for AICA aneurysms is also uncommon. 9 The AICA during its course has an abrupt turn at the internal auditory meatus and is in close relation to cranial nerve VII and VIII at that point. Common AICA-PICA trunk has similar course as that of AICA with the vessel dividing in rostral and caudal division.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8] Intrameatal location for AICA aneurysms is also uncommon. 9 The AICA during its course has an abrupt turn at the internal auditory meatus and is in close relation to cranial nerve VII and VIII at that point. Common AICA-PICA trunk has similar course as that of AICA with the vessel dividing in rostral and caudal division.…”
Section: Discussionmentioning
confidence: 98%
“…5 Small morphologic space makes surgical exposure critical with high complications. 1 Technical advances in endovascular procedures can make these treatment options as first-line treatment. Even though acute angulation of origin and tortuous anatomy can lead to difficult catheterization, we used balloon-assisted catheterization of the vessel for stable microcatheter position near the neck of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of aneurysms of the anterior inferior cerebellar artery (AICA) is approximately 0.1 to 0.5% among all intracranial aneurysms. 1 Recent review has reported only 21 cases of meatal segment AICA aneurysm. 2 Clinical presentation of these aneurysms varies from asymptomatic, isolated cranial nerve paralysis (VII and VIII) and rupture with acute subarachnoid hemorrhage (SAH).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data, angiograms in articles, management techniques, and patient outcomes were reviewed for 47 collected cases in 30 published reports. [1][2][3][4][5]7,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][31][32][33] AICA aneurysms associated with arteriovenous malformation (AVM) and Moyamoya disease were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Anterior inferior cerebellar artery (AICA) aneurysms are so rare that published experiences are limited to case reports and small patient series. 133 The description of AICA aneurysms in many of these reports is imprecise. 5,1012,3133 Several therapeutic options exist, encompassing microsurgical and endovascular techniques.…”
Section: Introductionmentioning
confidence: 99%